Thiamine Pyrophosphate Biosynthesis and Transport in the Nematode Caenorhabditis elegans - de Jong, Liesbeth (Genetics Society of America, 2004)
Thiamine (vitamin B1) is required in the diet of animals, and thiamine deficiency leads to diseases such as beri-beri and the Wernicke-Korsakoff syndrome. Dietary thiamine (vitamin B1) consists mainly of thiamine pyrophosphate (TPP), which is transformed into thiamine by gastrointestinal phosphatases before absorption. It is believed that TPP itself cannot be transported across plasma membranes in significant amounts. We have identified a partial loss-of-function mutation in the Caenorhabditis elegans gene (tpk-1) that encodes thiamine pyrophosphokinase, which forms TPP from thiamine at the expense of ATP inside cells. The mutation slows physiological rhythms and the phenotype it produces can be rescued by TPP but not thiamine supplementation. tpk-1 functions cell nonautonomously, as the expression of wild-type tpk-1 in one tissue can rescue the function of other tissues that express only mutant tpk-1. These observations indicate that, in contrast to expectation from previous evidence, TPP can be transported across cell membranes. We also find that thiamine supplementation partially rescues the phenotype of partial loss-of-function mutants of the Na/K ATPase, providing genetic evidence that thiamine absorption, and/or redistribution from the absorbing cells, requires the full activity of this enzyme.